New paradigms on siRNA local application - Pan, Meng (BMB Rep, 2015)
Small interfering RNA (siRNA) functions through pairing with specific mRNA sequences and results in the mRNA’s degradation. It is a potential therapeutic approach for many diseases caused by altered gene expression. The delivery of siRNA is still a major problem due to its rapid degradation in the circulation. Various strategies have been proposed to help with the cellular uptake of siRNA and short or small hairpin RNA (shRNA). Here, we reviewed recently published data regarding local applications of siRNA. Compared with systemic delivery methods, local delivery of siRNA/shRNA has many advantages, such as targeting the specific tissues or organs, mimicking a gene knockout effect, or developing certain diseases models. The eye, brain, and tumor tissues are ‘hot’ target tissues/organs for local siRNA delivery. The siRNA can be delivered locally, in naked form, with chemical modifications, or in formulations with viral or non-viral vectors, such as liposomes and nanoparticles. This review provides a comprehensive overview of RNAi local administration and potential future applications in clinical treatment. [BMB Reports 2015; 48(3): 147-152]